Hey, I've begun going through a book called "An introduction to geophysical exploration" by Phillip Kearey and Michael Brooks and I've come across a problem I can't for the life of me see how they got their answer. Essentially, given an input function gi (i = 1,2.... m), and a convolution operator fj (j = 1,2 ......n) the convolution output is given by: yk = [itex]\Sigma[/itex]gifk - i (k = 1,2 ..... m + n - 1) with (Sigma sum starting at i = 1 and going up to m). Their example is with an input of g(2,0,1) and operator of f(4,3,2,1) the output is y(8,6,8,5,2,1). Not only can I not see how this is obtained, but based on the function if I'm trying to find y1 I end up with negative index of fj as I perform fk - i as i increases from 1 to 3 with the largest index being f0 (from f1 - 1 where k = 1 and i = 1). How can this be correct? Any help would be appreciated.